2017
DOI: 10.18632/oncotarget.17174
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of SphK2 contributes to ATRA resistance in colon cancer through rapid degradation of cytoplasmic RXRα by K48/K63-linked polyubiquitination

Abstract: The resistance mechanisms that limit the efficacy of retinoid therapy in cancer are poorly understood. Sphingosine kinase 2 (SphK2) is a highly conserved enzyme that is mainly located in the nucleus and endoplasmic reticulum. Unlike well-studied sphingosine kinase 1 (SphK1) located in the cytosol, little has yet understood the functions of SphK2. Here we show that SphK2 overexpression contributes to the resistance of all-trans retinoic acid (ATRA) therapy in colon cancer through rapid degradation of cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…TCGA gene expression analysis revealed ER + breast cancer patients had elevated SphK2 transcripts compared to matched controls ( Figure 6A). SphK2 expression is also found elevated in other human cancers including NSCLC, 52 and colon cancer, 51 with targeting SphK2 with a selective inhibitor reducing lung cancer growth, 76 papillary thyroid carcinoma, 77 bladder cancer, 78 colorectal cancer, 79 and colon cancer, 80 with just one exception, 81 indicating SphK2 is a potentially good therapeutic target. 65 Our previous work also revealed SphK2/ S1P is essential for metastatic breast cancer cell growth and survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TCGA gene expression analysis revealed ER + breast cancer patients had elevated SphK2 transcripts compared to matched controls ( Figure 6A). SphK2 expression is also found elevated in other human cancers including NSCLC, 52 and colon cancer, 51 with targeting SphK2 with a selective inhibitor reducing lung cancer growth, 76 papillary thyroid carcinoma, 77 bladder cancer, 78 colorectal cancer, 79 and colon cancer, 80 with just one exception, 81 indicating SphK2 is a potentially good therapeutic target. 65 Our previous work also revealed SphK2/ S1P is essential for metastatic breast cancer cell growth and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Sphingosine kinase 2 expression has been found elevated in both colon cancer 51 and non-small cell lung cancer F I G U R E 5 SphK2 enhances HIF-1α binding to the VEGF promoter. MCF-7 cells (A, B) or MDA-MB-231 cells (C) transfected with siControl or siSphK2 were exposed to hypoxia (black bar) or normoxia (white bar) for 40 minutes.…”
Section: Analysis Of Expression Levels Of Sphk2 and Hif-1α In Humanmentioning
confidence: 99%
“…Indeed, sphingosine kinase 2 (SphK2) over-expression was found in colonic cancer cells resistant to retinoic acids [126]. The SphK2 mechanism of action induced the increase of RXRα translocation into the cytoplasm and then the rapidly degradation through the polyubiquitination pathway, so inhibiting the triggering of apoptosis (Figure 3) [127].…”
Section: Escape Routes From Apoptosismentioning
confidence: 99%
“…In agreement with this eventuality, studies have suggested that, when SphK2 is localized in the nucleus, it can inhibit the synthesis of DNA, thus exerting anti-proliferative effects ( Hait et al, 2009 ). Conversely, other contributions have shown that, in human colon carcinoma cells, S1P generated by nuclear SphK2 can inhibit the retinoic acid receptor β, attenuating the tumor suppressor effects of this receptor ( Shi et al, 2017 ).…”
Section: Structure and Function Of Sphingosine Kinasesmentioning
confidence: 99%